Regulation of α-Ketoglutarate levels by Myc affects metabolism and demethylation in porcine early embryos - Ding, Ran; Zhou, Yongfeng; Zhang, Qi; Kong, Xiangjie; Li, Qi; Zhang, Sheng; Chen, Yibing; An, Xinglan; Li, Ziyi (Frontiers in Cell and Developmental Biology, 2024)
The Myc family is essential for cell proliferation, differentiation, and metabolism, particularly in embryonic development and stem cell functions. However, the specific role of Myc in porcine early embryonic development is not fully understood. This study observed high Myc expression during the four-cell stage of porcine embryos. Inhibition of Myc using 10058-F4 impaired embryonic development, disrupted energy metabolism, and increased DNA methylation. Mechanistically, these effects were dependent on α-KG, a TCA cycle intermediate and cofactor for TET demethylation enzymes. Sequencing analysis of four-cell embryos post-Myc inhibition revealed downregulation of key metabolic enzymes related to α-KG, such as CS, IDH2, leading to reduced α-KG levels. Supplementation with α-Ketoglutarate (α-KG) mitigated the negative effects of Myc inhibition, including lower blastocyst rates, decreased ATP levels, and increased 5 mC levels. In conclusion, Myc regulates the expression of key metabolic enzymes during the four-cell stage, influencing early embryonic metabolism and epigenetic reprogramming.